A Linguistic Analysis of Rukiga Personal Names - Asiimwe, Allen (Journal of the Language Association of Eastern Africa, 2022)
The goal of the paper is to provide a linguistic description of the structure of personal names in a lesser studied Bantu language of Uganda, Rukiga (JE14). Data show that Rukiga personal names are presented as lexical entities but with underlying elaborate grammatical structures derived from the syntax, morphology, phonology and the lexicon of the language. Personal names in Rukiga form a special category of nouns derived from nouns, adjectives, verbs, phrases, clauses and full sentences. This study establishes that truncation, affixal derivation, lexicalization of phrases, clauses and sentences are employed in name-formation. The study further reveals that the socio-cultural context influences the semantics and structure of names in Rukiga. Data for this study were collected in Kabale district in western Uganda through interviewing older persons, reviewing religious documents and tax collection registers. The study mirrors personal names as a part of the grammar of Rukiga reflecting the general complex linguistic system of the language. Data from this study is envisaged to contribute to typological and theoretical analyses of personal names which have internal morphosyntactic properties.